Impact of fiscal decentralization and local government competition on the supply of basic public services: Based on the empirical evidence of prefecture-level cities in China - Yamei Wang; Xiuquan Huang; Tao Zhang; Bo Jiang; Xi Wang (Heliyon, 2024)
Promoting equal access to public services and improving people's well-being is a key link in building a modern national governance system in China. However, under the Chinese-style fiscal decentralization system, local governments face the “dilemma” of economic growth goals and the improvement of people's livelihoods. China's basic public services still have the problems of insufficient supply quantity, unbalanced structure and low efficiency. This paper aims to explore the impact of fiscal decentralization and local government competition on basic public services, and provide a theoretical and practical basis for deepening the reform of China's fiscal and taxation system, perfecting the transfer payment system, and improving the public service provision at the present stage. Under the premise of theoretical hypothesis, based on the panel data of 178 prefecture-level cities in China from 2008 to 2019, which is obtained from the Statistical Yearbook and the Work report of prefecture-level governments, the fixed effect model and threshold model are used for the empirical test. The results show that: first, the increase of fiscal decentralization has a negative impact on supply of basic public services in prefecture-level cities; second, the local government competition aiming at economic growth will intensify the negative impact, and make the relationship between fiscal decentralization and basic public services show nonlinear characteristics; Third, compared with developed areas, the strengthening regulatory effect of local government competition is more obvious in less-developed areas, such as western and northeastern regions, and third-tier, fourth-tier, and fifth-tier cities. Based on these findings, this paper draws the following policy implications: strengthen the reform of the fiscal and taxation system below the provincial level, promote the construction of a direct transfer payment mechanism, adjust the standards and methods of performance appraisal, and use modern information technology to improve the public service demand and interest expression mechanisms.